Manajemen Pembelajaran Menghafal Al-Quran Di SMP IT Nurul Fadhilah - Lioni Kurnia Sari (Al-Ulum: Jurnal Pendidikan Islam, 2023)
This study aims to determine the Learning Management of Memorizing Al-Quran in SMP IT Nurul Fadhilah. This study uses a descriptive qualitative research method. Data collection techniques used are: observation, interviews, and documentation. Data analysis techniques namely data collection, data condensation, data presentation, data analysis and conclusions. The results of research conducted at SP IT Nurul Fadhilah is that the management of learning to memorize the Al Quran has been carried out in accordance with management functions, namely management of planning, organizing, implementing, and evaluating. Planning is carried out by considering the learning objectives, methods, materials, time, target memorization, and assessment, which are outlined in the syllabus made by the teacher in charge. Organizing is done by handing over responsibility for learning activities to the school principal who is then delegated to the learning coordinator and teachers. Implementation of learning is divided into two groups, namely tahsin and tahfiz with the allocation of special days for reading, memorizing, and murojaah. Evaluation is carried out by testing students' abilities using rote test techniques and practical tests.